The Incidence of Hepatocellular Carcinoma Is not Increased in Individuals with Chronic Hepatitis C After Treatment with Interferon-free Regimens: an ERCHIVES Study. (4th October 2017) - Li, Darrick K; Ren, Yanjie; Saikh, Obaid; Fierer, Daniel S; Re, Vincent Lo; Abou-Samra, Abdul-Badi; Chung, Raymond T; Butt, Adeel
Abstract: Background: Sustained virologic response (SVR) after interferon-based treatment for chronic hepatitis C virus (HCV) infection has been strongly linked with decreased incidence of hepatocellular carcinoma (HCC). Surprisingly, several recent studies have reported higher rates of HCC in individuals treated with direct-acting antivirals (DAAs). However, making definitive conclusions has been challenging due to the heterogeneous populations and methodologies of these reports. As such, we sought to investigate whether DAA use is associated with increased rates of incident HCC. Methods: Using the Electronically Retrieved Cohort of HCV Infected Veterans (ERCHIVES) database, we identified 17, 836 patients without a prior diagnosis of HCC and divided them into 3 groups based on treatment: (a) pegylated interferon and ribavirin (IFN) ( n  = 3, 534); (b) DAA-based therapy ( n  = 5, 734); and (c) an untreated control group ( n  = 8, 468). Predictors of HCC were identified using multivariate Cox proportional hazards analysis. HCC-free survival in cirrhotics was assessed by Kaplan–Meier analysis. Results: SVR was achieved by 66.6% and 96.2% of the IFN and DAA groups, respectively. In our cohort, the incidence rate of HCC was not different between IFN and DAA groups (7.48/1000 vs. 7.92/1000 patient-years of follow-up; P  = 0.72). Moreover, DAA treatment was not associated with an increased risk of HCC (HR 1.16; [95% CI: 0.79, 1.71]) compared to IFN treatment. Other risk factors for HCC included older age, alcohol abuse/dependance history, smoking history, HCV genotype 3 infection, proton-pump inhibitor use, AFP > 20, and cirrhosis. Notably, among cirrhotics who achieve SVR, HCC-free survival was not different between IFN and DAA treated groups, and both groups had significantly improved HCC-free survival compared with untreated patients. Conclusion: Among cirrhotic patients with HCV, DAA treatment is associated with a comparable risk of HCC to IFN treatment. Furthermore, the rate of HCC after SVR by any treatment was significantly lower than for those untreated or who failed to achieve SVR. Previously reported increases in HCC associated with DAA treatment appear to be explained by the presence of pre-existing risk factors for HCC. Disclosures: R. T. Chung, Gilead: Investigator, Research grant; Abbvie: Investigator, Research grant; Merck: Investigator, Research grant; Janssen: Investigator, Research grant; A. Butt, Merck: Investigator, Grant recipient